DRPs (DRUG RELATED PROBLEMS) PADA PENDERITA DIABETES MELLITUS DENGAN KOMPLIKASI GAGAL GINJAL DI RUMAH SAKIT UMUM DAERAH ‘X’ DI SAMARINDA PERIODE OKTOBER-DESEMBER 2016 - Rusdiati Helmidanora; Muhammad Reza; Yullia Sukawaty (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Drug Related Problems (DRPs) is an unexpected event from the patient's experience because drug therapy can interfere with the success of healing. Patients with chronic disease for a long time have a chance of developing DRP. One chronic disease is diabetes mellitus which is a metabolic disorder due to lack of insulin production produced by the pancreas gland. Diabetic nephropathy is a microvascular complication that often occurs in type 1 and type 2 diabetes, due to high blood sugar levels that can cause kidney structure to change and impaired function. The aim of this study was to determine DRP in patients with diabetes with kidney failure. Research conducted was non-experimental research with data collection retrospectively. The data were analyzed by using standard reference books, Drug Information Handbooks. Based on the results of the study found DRPs in patients with DM with kidney failure in the inpatient installation of RSUD 'X' Samarinda in the period October-December 2016 who needed drugs but did not receive it (24%), received drugs without appropriate indications (11%), received wrong drugs (3%), dose was too low (0%), dose was too high (5%), the patient has ADR (13%), and compliance (0%).